(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Today, studying the history of the Samarkand city and its historical monuments , which has its rightful place in introducing the name of Uzbekistan to the world , is one of the main directions for historians. This article talks about the opinions and comments are given about the extensive construction works of Yalangtush Bakhodir carried out in Samarkand during the his governorship, the construction of Sher-dar and Tilya-kari madrasahs in the Registan ensemble.